Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: S=1(1+1)+2(1+2)+...+100(1+100)
=1+2+...+100+1^2+2^2+...+100^2
\(=\dfrac{100\cdot102}{2}+\dfrac{100\cdot\left(100+1\right)\cdot\left(2\cdot100+1\right)}{6}\)
\(=100\cdot51+\dfrac{100\cdot101\cdot201}{6}\)
=343450
b: \(A=1\cdot2\cdot3+2\cdot3\cdot4+...+100\cdot101\cdot102\)
=>\(4\cdot A=1\cdot2\cdot3\cdot\left(4-0\right)+2\cdot3\cdot4\left(5-1\right)+...+100\cdot101\cdot102\left(103-99\right)\)
=>4*A=100*101*102*103
=>A=25*101*102*103
Ta có: (x1+x2)+(x3+x4)+...+(x99+x100)+x101=0 (50 nhóm)
=1x50+x101=0
=50 + x101=0
x101=0-50=-50
1
b;
B=1+ (7-5) + (11-9) + ...+(101-99)
B=1+2+2+..+2
B=1+25.2=51
2.
a.
ĐK : x+2 >=0 => x>=-2
\(\left|x+2\right|-x=2\\ \Rightarrow\left|x+2\right|=2+x\\ \Rightarrow\left[{}\begin{matrix}x+2=x+2\\x+2=-x-2\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}0x=0\\2x=-4\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}0x=0\\x=-2\end{matrix}\right.\)
Vậy x=-2
(x+1)+(x+3)+(x+3^2)+...+(x+3^99)+(x+3^100)=3^101
=>x+1+x+3+x+3^2+...+x+3^99+x+3^100=3^101
=>(x+x+...+x) + (1+3+3^2+...+3^100) = 3^101
101 lần
=>101.x + (1+3+3^2+...+3^100) = 3^101.
Đặt A = 1 + 3 + 3^2 + ... + 3^100
=> 3A = 3.(1 + 3 + 3^2 + ... + 3^100)
=> 3A = 3 + 3^2 + 3^3 + ... + 3^101
=> 3A - A = 3 + 3^2 + 3^3 + ... + 3^101 - 1 - 3 - 3^2 - ... - 3^100
=> 2A = 3^101 - 1
=> A = (3^101 - 1)/2
Thay A = (3^101 - 1)/2 vào trên, ta có:
101.x + (3^101 - 1)/2 = 3^101
=>101x = 3^101 - (3^101-1)/2
=> x = [3^101 - (3^101 - 1)/2]/101
( x + 1 ) + ( x + 2 ) + ( x + 3 ) + ... + ( x + 101 ) = 9780
( x + x + x +... + x ) + ( 1 + 2 + 3 + ... + 101 ) = 9780
x * 101 + 5151 = 9780
x * 101 = 9780 - 5151
x * 101 = 4629
x = 4629 : 101
x = 45,83